'It Makes You Sit Back and Think Where You Wanna Go': Veteran experiences in virtual whole health peer‐led groups - Ekaterina Anderson; Kelly Dvorin; Bella Etingen; Anna M. Barker; Zenith Rai; Abigail N. Herbst; Reagan Mozer; Rodger P. Kingston; Barbara G. Bokhour (Wiley, 2022)
Abstract Background The Veterans Health Administration (VHA) is building a Whole Health system of care that aspires to empower and equip each Veteran to pursue a personally meaningful vision of health and well‐being. As part of this effort, VHA has developed Taking Charge of My Life and Health (TCMLH), a peer‐led, group‐based programme that seeks to support Veterans in setting and pursuing health and well‐being goals. Prior research showed TCMLH groups to positively impact Veteran outcomes; yet, little is known about Veterans' own experiences and perspectives. Methods We completed semi‐structured telephone interviews with 15 Veterans across 8 sites who had participated in TCMLH groups offered by the VHA in the virtual format between Summer 2020 and Fall 2021. Inductive thematic analysis was applied to interview transcripts to generate themes. Findings We identified five themes regarding Veterans' experiences with TCMLH: (1) navigating the virtual format; (2) internalizing the value of health engagement; (3) making healthy lifestyle changes; (4) forging social connections; and (5) taking on a more active role in healthcare. Conclusion Veterans perceived virtual TCMLH groups as meaningful and beneficial, yet also highlighted several challenges. Their perspectives speak to the need to supplement time‐limited programmes like TCMLH with ongoing, community‐based support. Virtual group‐based well‐being programmes are a promising innovation. Other healthcare systems may draw on VHA's experience while tailoring format and content to the needs of their patient populations. Patient or Public Contribution Veterans were involved as evaluation participants. A Veteran consultant, who is a coauthor on this paper, was engaged through the conceptualization of the evaluation, development of data collection materials (interview guide) and writing.